The impact of migration-related characteristics on the risk of TORCH infections among women of childbearing age: a population-based study in southern China - Rui Li; Lu Han; Wenxue Xiong; Wenjuan Wang; Chaonan Fan; Mingzhen Li; Xiaohua Liu; Li Ling (BMC, 2023)
Abstract Background TORCH infections are the most common prenatal infections causing congenital malformation and infant mortality, especially in developing countries. Migrant women might be vulnerable to TORCH infections, but little is known about the association between migration-related characteristics and TORCH infection risk. This study aimed to investigate the impact of migrant status, migration distance, and the spouse's migrant status on the TORCH epidemic among women of childbearing age. Methods Based on the National Free Preconception Health Examination Project, we analyzed a representative dataset of TORCH infections among women of childbearing age (15-49 years old) in Guangdong Province of China (2014-2019, n = 2,451,297). The past and/or recent infection status of TORCH infections (Toxoplasma gondii [TOX], Cytomegalovirus [CMV], and Rubella virus [RV]) were identified. Demographic and migration-related characteristics were collected. We thoroughly assessed the prevalence of TORCH infections in both migrant and native women and estimated adjusted odd ratios (aOR) for migration-related characteristics using multivariable logistic regression after adjusting the other sociodemographic factors. Results Among all 2,451,297 participants, 443,725 (18.1%) were migrant women. Migrant women presented a lower risk of past TOX infection (aOR: 0.89, 0.88-0.91) suggesting a healthy migrant effect (HME), but a higher risk of recent TOX infection (aOR: 1.88, 1.77-1.99), past CMV infection (aOR: 1.26, 1.25-1.28) and RV infection in natural ways (aOR: 1.05, 1.04-1.06). Compared with intra-provincial migrants, inter-provincial migrants had a lower past TOX infection (aOR: 0.88, 0.85-0.91), but a higher risk of recent TOX infection (aOR: 1.16, 1.05-1.27) and RV infection (aOR: 1.33, 1.31-1.36). In addition, having a migrant spouse was associated with a higher risk for all types of infection. Conclusion This study reported the association of migrant status and migration distance with TORCH infections, although the significance and directionality of these associations varied between pathogens. The spouse's migrant status further amplified the infection risk for all types of pathogens. Our findings suggested interventions for preventing the spread of CMV and RV infection and new acquisition of TOX infection for migrants in southern China, to narrow the native-migrant health inequity and decrease the incidence of prenatal infections and related adverse outcomes.